The influence of kaizen behavior, OCB, and organizational commitment on employee job satisfaction at Sidoarjo Station - Achmad, Ak’yas Daksani; Zaki, Achmad (Institute of Computer Science (IOCS), 2025)
Kaizen culture, OCB and organizational commitment have been identified as three synergies that have an important influence in influencing employee job satisfaction, the importance of effective human resource management in order to achieve planned quality success. Kaizen is long-term and sustainable towards change, while OCB encourages voluntary behavior and organizational commitment to the extent to which the company has an emotional attachment to employees. The aim of this research is to describe numerically the extent of the overall influence of the variables that have been used as context in this research. A quantitative model with a descriptive approach was chosen to make it easier to explain statistical analysis by researchers using the total sample of employees working at Sidoarjo Station 1 as well as an assessment instrument using Linkert guidelines. The results of this research show that kaizen culture has a significant influence on employee satisfaction, as well as OCB and organizational commitment also have a significant influence on employee satisfaction which has been supported through testing the t-partial and f-simultaneous hypotheses.